Effect of physical and chemical mutagens on morphological behavior of tomato (Solanum Lycopersicum) CV. - Akhtar, Naheed (Plant Breeding and Seed Science, 2014)
Given the importance to tomato production under heat stress conditions in hot climates of Pakistan, the objective of this research work was to study the influence of temperature and application of physical and chemical mutagens on tomato (Lycopersicon esculentum L.,) CV. “Rio grande” Seeds were treated with chemical mutagen (Ethyl Methane Sulphonate) and physical mutagen (Gamma radiation) . Plants were grown in open field conditions under day/night temperatures regimes at the experimental area of Department of Horticulture, faculty of crop and food sciences, PMAS-AAUR. The experiment was set twenty treatments and four replications in Complete Randomize Block Design. It is observed that by increasing dose of mutagens shows lethal effect and morphological parameters reduced significantly. But lower doses of EMS and Gamma radiation improve thermotolerance capacity significantly. Plants were investigated for different morphological parameters i.e Plant height, no. of leaves, leaf area, relative water contents of leaves, chlorophyll contents, cell viability (TCC Assay) and pollen germination. Among gamma rays 5Kr were the only dose which survived and bear fruits. Among EMS 4mM, 8 mM, 16mM performed better under heat stress conditions than other treatments